Development of an Antibiotic Resistance Breaker to Resensitize Drug-Resistant Staphylococcus aureus: In Silico and In Vitro Approach - Thamilselvan, Gopalakrishnan; Sarveswari, Hema Bhagavathi; Vasudevan, Sahana; Stanley, Alex; Shanmugam, Karthi; Vairaprakash, Pothiappan; Solomon, Adline Princy (Frontiers in Cellular and Infection Microbiology, 2021)
Efflux pumps are one of the predominant microbial resistant mechanisms leading to the development of multidrug resistance. In Staphylococcus aureus, overexpression of NorA protein enables the efflux of antibiotics belonging to the class of fluoroquinolones and thus makes S. aureus resistant. Hence, NorA efflux pump are being extensively exploited as the potential drug target to evade the bacterial resistance and re-sensitize bacteria to the existing antibiotics. Although, several molecules are reported to inhibit NorA efflux pump effectively, boronic acid derivatives were shown to have promising NorA efflux pump inhibition. In this regard, the current study exploits 6-(3-phenylpropoxy)pyridine-3-boronic acid to further improve the activity and reduce cytotoxicity using the bioisostere approach, a classical medicinal chemistry concept. Using SWISS-Bioisostere online tool, from the parent compound, 42 compounds were obtained upon the replacement of the boronic acid. The 42 compounds were docked with modelled NorA protein and key molecular interactions of the prominent compounds were assessed. The top hit compounds were further analysed for their drug like properties using ADMET studies. The identified potent lead, 5-nitro-2-(3-phenylpropoxy)pyridine (5-NPPP) was synthesized and the in vitro efficacy studies proven to show enhanced efflux inhibition, thus acting as potent antibiotic breaker to resensitize S. aureus without elucidating any cytotoxic effect to the host, Hep-G2 cell lines.